2015
DOI: 10.1007/s10551-015-2758-2
|View full text |Cite
|
Sign up to set email alerts
|

Do Lenders Applaud Corporate Environmental Performance? Evidence from Chinese Private-Owned Firms

Abstract: This study extends previous literature on the association between corporate social responsibility and corporate financial behavior by investigating the influence of corporate environmental performance on the cost of debt. Using a sample of Chinese private-owned firms, we document strong and consistent evidence to show that corporate environmental performance is significantly negatively associated with the interest rate on debt-the proxy for the cost of debt. The findings suggest that lenders applaud better env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 88 publications
(204 reference statements)
4
54
0
Order By: Relevance
“…Existing studies have employed a content analysis index to measure EID (Du, Weng, Zeng, Chang, & Pei, ). In China, EID guidelines have been issued by the government, such as The Guidelines for Environmental Information Disclosure of Listed Companies issued by Shanghai Stock Exchange in 2008 and The Guidelines for Environmental Information Disclosure of Listed Companies (Draft for Comments) issued by the Ministry of Ecology and Environment, formerly the Ministry of Environmental Protection of China, in 2010.…”
Section: Methodsmentioning
confidence: 99%
“…Existing studies have employed a content analysis index to measure EID (Du, Weng, Zeng, Chang, & Pei, ). In China, EID guidelines have been issued by the government, such as The Guidelines for Environmental Information Disclosure of Listed Companies issued by Shanghai Stock Exchange in 2008 and The Guidelines for Environmental Information Disclosure of Listed Companies (Draft for Comments) issued by the Ministry of Ecology and Environment, formerly the Ministry of Environmental Protection of China, in 2010.…”
Section: Methodsmentioning
confidence: 99%
“…Hypotheses 7 and 8 are related to many research results that indicated that corporate environmental performance management was influenced by the environmental behavior of the government environmental departments, investors, and the public [38,43,46,48]. In recent years, the government, society, and the public have demanded better environmental protection and have insisted that for any new fixed asset investment projects, enterprises must ensure environmental protection to stop the common enterprise free-riding behaviors.…”
Section: Hypothesismentioning
confidence: 98%
“…Du et al . () study the effect of CEP on the debt interest rate for private firms in China and demonstrate that there is a significant negative correlation between the two. This negative relation is weakened by the firms’ internal control information.…”
Section: Introductionmentioning
confidence: 99%